Monitoring of hepatitis E virus infection and replication by functional tagging of the ORF2 protein - Maliki Ankavay; Nathalie Da Silva; Angela Pollán; Noémie Oechslin; Katja Dinkelborg; Patrick Behrendt; Darius Moradpour; Jérôme Gouttenoire (JHEP Reports)
Background and Aims: Hepatitis E virus (HEV) infection is a leading cause of acute hepatitis worldwide. Understanding of the mechanisms underlying productive HEV infection remains incomplete and would benefit from technological advances improving current model systems. Methods: We exploited transposon-mediated random insertion and selection of viable clones to identify sites in the HEV open reading frame 2 (ORF2) protein, corresponding to the viral capsid, allowing for the insertion of reporter sequences in a functional context. Results: Short sequence insertions (5 amino acids) were tolerated at four distinct sites in the C-terminal region of the ORF2 protein, without significantly affecting viral capsid expression and subcellular localization as well as virus production. Full-length HEV genomes harboring larger sequence insertions such as an HA epitope tag, a highly sensitive miniaturized luciferase reporter (HiBiT) or a split GFP at these sites conserved their ability to produce infectious virus, with about a 1-log decrease in viral titers. Findings were confirmed in two different HEV genotype 3 clones. In addition, we demonstrate that HiBiT-tagged HEV, offering rapid and several-log amplitude detection, can be used for the evaluation of antiviral drugs and neutralizing antibodies. Conclusions: We describe a convenient, quantitative and potentially scalable system for the monitoring of HEV infection and replication in tissue culture. Impact and implications:: Hepatitis E virus infection is one of the most frequent causes of acute hepatitis and jaundice worldwide. As treatment options are limited and a vaccine is not universally available, the development of molecular tools to facilitate the identification of new therapeutic strategies is crucial. Based on a screening approach to identify viable insertion sites in the viral genome, we describe a versatile system for preparing recombinant viruses harboring split-reporter tags, i.e. luciferase and GFP. Proof-of-concept experiments revealed that convenient and quantitative monitoring of viral infection and replication is possible with this system, allowing for the evaluation of antiviral drugs and neutralizing antibodies.